THE ROLE OF SOCİOCULTURAL AND ECONOMİC FACTORS İN BRİNGİNG DİSADVANTAGED WOMEN İNTO EMPLOYMENT (Third Sector Social Economic Review, 2024)
This study aims to examine in detail the concept of disadvantage and how discrimination against women takes place in employment policies in Turkey. The role of sociocultural and economic factors in the employment of disadvantaged women is also one of the main focus points of the study. Disadvantage refers to the deprivation of social and economic advantages of individuals or groups, and in this context, women are among various disadvantaged groups such as the disabled, children and the elderly. Women's participation in the workforce in Turkey is limited by various barriers such as socioeconomic factors and gender roles. There are difficulties in women's inclusion in working life, such as gender-based discrimination in the labor market, glass ceiling syndrome and working conditions not being arranged in accordance with gender. In addition, the low level of education of women and the lack of perception of gender equality further reinforce inequality in employment. In the economic context, factors that make it difficult for disadvantaged women to find employment include high unemployment rates, wage differences and periods of economic crisis. Poverty, inequality of educational opportunities and difficulties in accessing health services also contribute to women's disadvantage in the labor market. From a socio-cultural perspective, in order to increase women's participation in the workforce, it is necessary to work on traditional gender roles and prejudices, promote gender equality and facilitate women's access to education and career opportunities. As a result of the study, it was concluded that ensuring the integration of disadvantaged women into the labor market is possible with the combination of sociocultural and economic factors. Implementing policies such as education and vocational training programs, flexible working hours, improving child care services and encouraging women's entrepreneurship stand out as other factors that will allow women to take a more active and equal role in business life.
Keywords: Disadvantage; Women's Employment; Sociocultural Factors; Economic Factors; Discrimination and Prejudice.